PEMBERDAYAAN PENGAWAS MINUM OBAT (PMO) TABLET TAMBAH DARAH IBU HAMIL DI PUSKESMAS SEKIP PALEMBANG - Dian Lestari; Heni Sumastri; Sari Wahyuni (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Anemia occurs at all stages of the life cycle, but is common in pregnant women and children. Data from the World Health Organization (WHO), the frequency of anemia in pregnant women in 1993 was 69.0%, non-pregnant women were 73.5%. ). The most common program used to control iron deficiency in developing countries today is the administration of iron supplements in pregnant women. (WHO, 2001). Based on the Basic Health Research, the incidence of anemia in Indonesia in 2007 was around 24.5%. Data from the Provincial Health Office in 2011, the national coverage of giving Fe tablets was 83.3%, this figure was below the national target of 86%). Obedience of pregnant women to take iron pills is an important factor in ensuring the increase in hemoglobin levels of pregnant women. Previous data studies have shown the effect of drug-taking supervisors on anemic pregnant women on the increase in Hb, p value = 0.001This community service activity uses a community participatory method. The results obtained are an increase before mentoring, the average knowledge is good 30%, very positive attitude is 40%, after mentoring good knowledge is 80%, and very positive attitude is 90 %.